2022
DOI: 10.3390/computers11030039
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Text-to-Image Encryption-Decryption Algorithm for Secure Network Communication

Abstract: Data security is the science of protecting data in information technology, including authentication, data encryption, data decryption, data recovery, and user protection. To protect data from unauthorized disclosure and modification, a secure algorithm should be used. Many techniques have been proposed to encrypt text to an image. Most past studies used RGB layers to encrypt text to an image. In this paper, a Text-to-Image Encryption-Decryption (TTIED) algorithm based on Cyan, Magenta, Yellow, Key/Black (CMYK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…From these discussions, it could be concluded that data size is proportional to the decryption time for Salsa20, Chaca20, and ERSA as indicated in Table 2. This makes their trend of decryption time deterministic, predictable, and linear which is supported by the works of [44,51]. With a linear trend of decryption time, hackers can predict, intercept and modify data [52].…”
Section: Plos Onementioning
confidence: 93%
“…From these discussions, it could be concluded that data size is proportional to the decryption time for Salsa20, Chaca20, and ERSA as indicated in Table 2. This makes their trend of decryption time deterministic, predictable, and linear which is supported by the works of [44,51]. With a linear trend of decryption time, hackers can predict, intercept and modify data [52].…”
Section: Plos Onementioning
confidence: 93%
“…It protects the image while it is being transmitted over a public network. Using the secret keys and decryption technique, only an authorized person can acquire the original image in this procedure [20].…”
Section: Image Processing and Image Encryption Terminologiesmentioning
confidence: 99%
“…Images sent over the internet are vulnerable to eavesdropping, tampering, unauthorized duplication, and other forms of theft because they are sent in clear text. With today's heavy reliance on electronic communication networks, protecting private information is more important than ever [3]. In light of this, there has been an increased focus in recent years on protecting the image in an effective manner.…”
Section: Introductionmentioning
confidence: 99%